2023
DOI: 10.3390/jpm13030558
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sex and Gender on Clinical Management of Patients with Advanced Chronic Liver Disease and Type 2 Diabetes

Abstract: Gender differences in the epidemiology, pathophysiological mechanisms and clinical features in chronic liver diseases that may be associated with type 2 diabetes (T2D) have been increasingly reported in recent years. This sexual dimorphism is due to a complex interaction between sex- and gender-related factors, including biological, hormonal, psychological and socio-cultural variables. However, the impact of sex and gender on the management of T2D subjects with liver disease is still unclear. In this regard, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 182 publications
0
1
0
Order By: Relevance
“…Besides the pathogenetic background, the finding of a higher risk of liver fibrosis in unaware T2D obese patients should prompt physicians to investigate liver damage in these patients, also in light of their correct management. Thus, although no medical treatment has been currently authorized for the management of NAFLD in patients with T2D, a growing body of evidence points to the beneficial effects of insulin-sensitivity drugs, such as pioglitazone, metformin, GLP-1RAs, and SGLT2i, irrespective of their beneficial effect on body weight [52][53][54]. In particular, a recent meta-analysis showed that treatment with GLP-1RAs was associated with significant reductions in the absolute percentage of liver fat content, serum liver enzyme levels, and a greater histological resolution of NASH without worsening liver fibrosis compared to placebo or reference therapies, indicating the great potential of this class of drugs for the treatment of T2D patients with NAFLD [55].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the pathogenetic background, the finding of a higher risk of liver fibrosis in unaware T2D obese patients should prompt physicians to investigate liver damage in these patients, also in light of their correct management. Thus, although no medical treatment has been currently authorized for the management of NAFLD in patients with T2D, a growing body of evidence points to the beneficial effects of insulin-sensitivity drugs, such as pioglitazone, metformin, GLP-1RAs, and SGLT2i, irrespective of their beneficial effect on body weight [52][53][54]. In particular, a recent meta-analysis showed that treatment with GLP-1RAs was associated with significant reductions in the absolute percentage of liver fat content, serum liver enzyme levels, and a greater histological resolution of NASH without worsening liver fibrosis compared to placebo or reference therapies, indicating the great potential of this class of drugs for the treatment of T2D patients with NAFLD [55].…”
Section: Discussionmentioning
confidence: 99%